2010
DOI: 10.5194/acp-10-6617-2010
|View full text |Cite
|
Sign up to set email alerts
|

Moisture effects on carbon and nitrogen emission from burning of wildland biomass

Abstract: Abstract. Carbon (C) and nitrogen (N) released from biomass burning have multiple effects on the Earth's biogeochemical cycle, climate change, and ecosystem. These effects depend on the relative abundances of C and N species emitted, which vary with fuel type and combustion conditions. This study systematically investigates the emission characteristics of biomass burning under different fuel moisture contents, through controlled burning experiments with biomass and soil samples collected from a typical alpine … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
87
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(90 citation statements)
references
References 32 publications
3
87
0
Order By: Relevance
“…This could also explain the more elevated estimated average EF value for CO, since generally fuel with a higher humidity decreases the combustion efficiency, reduces the flaming phase, and causes a smoldering phase before ignition. In addition, it results in an increase of the emission factors for species resulting from incomplete oxidation, such as CO [39]. Yokelson et al [24] explained that a high MCE was obtained from a laboratory fire that burned at a MCE that was higher than that normally obtained in the field for biomass burning and, in this way, the MCE of a typical sugarcane fire is likely lower and would imply a larger emission factor for PM 2.5 .…”
Section: Resultsmentioning
confidence: 99%
“…This could also explain the more elevated estimated average EF value for CO, since generally fuel with a higher humidity decreases the combustion efficiency, reduces the flaming phase, and causes a smoldering phase before ignition. In addition, it results in an increase of the emission factors for species resulting from incomplete oxidation, such as CO [39]. Yokelson et al [24] explained that a high MCE was obtained from a laboratory fire that burned at a MCE that was higher than that normally obtained in the field for biomass burning and, in this way, the MCE of a typical sugarcane fire is likely lower and would imply a larger emission factor for PM 2.5 .…”
Section: Resultsmentioning
confidence: 99%
“…Detailed descriptions of these different techniques can be found in the literature (Ward and Radke, 1993;Yokelson et al, 1999;Christian et al, 2004). For real-time concentration measurements, the analytical instruments must be close to the fire.…”
Section: Different Measurement Approaches and Techniquesmentioning
confidence: 99%
“…Chen et al, 2010). Qualitatively, important parameters that partly govern the flaming/smoldering ratio and thus EFs include vegetation characteristics, climate, weather, topography, and fire practices.…”
Section: Factors Influencing the Efmentioning
confidence: 99%
“…Furthermore, there has been limited study of the effect of straw burning conditions (e.g., moisture of rice straw or size of rice straw stacks) on the amount of each gas emitted during straw burning. Since the moisture content of burned biomass affects carbon (C) and nitrogen (N) emissions (Chen et al 2010) and emissions factors -for example, residue moistness has been shown to be positively correlated with particle emissions (Darley et al 1974;Oanh et al 2011)-the effects on the burned straw condition also need to be taken into account when considering regional GHG emissions. High moisture content was shown to enhance the emissions of gases that originated from incomplete combustion, typically CO (Hayashi et al 2014).…”
Section: Introductionmentioning
confidence: 99%